Biogeography and Prehistoric Exploitation of Birds from Fais Island, Yap State, Federated States of Micronesia - D. W. Steadman; Intoh, M. (Pacific Science, 1994)
Five archaeological sites on the remote, raised limestone island of Fais, Yap, Federated States of Micronesia, yielded nearly 200 identifiable bird bones from strata that range in age from about 400 to 1800 radiocarbon yr B.P. Represented are 14 species of seabirds, five species of migratory shorebirds, four species of land birds, and the introduced chicken. This is the most species-rich prehistoric assemblage of birds from any island in Micronesia. Because the "modern" avifauna of Fais never has been studied, it is difficult to determine which of the species from archaeological contexts still occur on Fais. Nevertheless, based upon modern distributions of birds from other islands in Yap and adjacent island groups, the environmental condition of Fais, and what is known about the relative vulnerability of individual species, it is likely that about nine of the seabirds (Pterodroma sp., Bulweria bulwerii, Sula dactylatra, S. sula, Sterna sumatrana, S. lunata, S./uscata, Anous minutus, Procelsterna cerulea) and three of the land birds (Poliolimnas cinereus, Gallicolumba cf. xanthonura, Ducula oceanica) no longer live on Fais..
Keywords: anthropology biology